Nutzerorientiertes Energiedatenmanagement - Rigoll, Fabian (KIT Scientific Publishing, 2017)
Energy data often is critical data which can negatively affect users' privacy. Therefore, this work presents a user-oriented energy data management system which does not only comply with technical requirements but also lives up to users' demands in terms of privacy and data protection.